Dead and Gone - Harris, Charlaine (New York : Ace Books, 2009)
In Bon Temps, Louisiana, a race of unhuman beings--older, more powerful and far more secretive than vampires or werewolves-- is preparing for war. And Sookie Stackhouse will find herself an all-too human pawn in their battle as she investigates the murder of a were-panther.
Keywords: Vampires; Werewolves; Occult fiction; Mystery fiction